PERAN KEPEMIMPINAN KONTAK TANI DALAM PROSES DIFUSI INOVASI TEKNOLOGI PENGELOLAAN TANAMAN DAN SUMBERDAYA TERPADU PADI - Pertiwi, Pepi Rospina (Jurnal Matematika Sains dan Teknologi, 2012)
Farmers group is lead by a farmer leader that was expected to improve a dynamic of group activities. The farmer leader has significant role in ensuring the relationship between farmers in relation to the information sharing of the agricultural innovation. This study was aimed to examine the leadership role of the farmer leaders in the process of technology diffusion namely PTT Paddy, an innovation that was currently being introduced. An explanatory research design was chosen to describe the phenomenon of the leadership role of farmer leaders that was evaluated by other farmers. The research was conducted in the subdistrict Carenang, Serang, Banten. Forty participants in successfull farmer groups were selected to evaluate farmer leadership characteristics. The results showed that the farmer leaders have been helping the group to achieve goals, improving communication, increasing the motivation of the farmers, facilitating the farming infrastructure, and solving problems. The role of the farmer leaders as bridging agent in communication is categorized satisfactory. This role is effectively used in the process of the innovation dissemination of PTT Paddy to the farmers. Kelompok tani dipimpin oleh seorang kontak tani yang diharapkan dapat meningkatkan dinamika kegiatan kelompok. Kontak tani memiliki peran penting dalam memastikan hubungan antara petani dengan berbagi informasi mengenai inovasi pertanian. Penelitian ini bertujuan untuk meneliti peran kontak tani dalam proses difusi teknologi yaitu Pengelolaan Tanaman dan Sumberdaya Terpadu (PTT) Padi, sebuah inovasi yang saat ini sedang diperkenalkan. Desain penelitian adalah eksplanatory research dipilih untuk menggambarkan fenomena peran kontak tani yang dievaluasi oleh petani lain. Penelitian dilakukan di Kecamatan Carenang, Serang, Banten. Empat puluh peserta dalam kelompok tani terpilih untuk mengevaluasi karakteristik kontak tani. Hasil penelitian menunjukkan bahwa kontak tani telah membantu kelompok untuk mencapai tujuan, meningkatkan komunikasi, meningkatkan motivasi petani, memfasilitasi infrastruktur pertanian, dan memecahkan masalah. Peran kontak tani sebagai agen penghubung dalam komunikasi dikategorikan memuaskan. Peran ini efektif digunakan dalam proses penyebaran inovasi PTT padi ke petani.